Qualitative Properties of a Model for Carrier Facilitated Groundwater Contaminant Transport - Knabner, Peter; Schneid, Eckhard (Scientific Computing in Chemical Engineering, 1996)
Contaminants with very low water solubilities (e.g. polycyclic aromatic hydrocarbons) play an important role in risk assessment of dangerous wastes and development of soil remediation. The mobility of such hydrophobic substances can be strongly affected by the existence of carriers (e.g. dissolved organic carbon), which can adsorb the contaminant and thereby enhance or reduce its velocity. The numerical simulation of the spreading of these contaminants, requires the solution of reactive transport equations for all involved components, coupled by the contaminant’s sorption to the carrier. Our development is based on a model [2], in which all the carrier’s influence on the contaminant transport is contained in an effective adsorption isotherm, depending on the carrier concentration and thereby also on space and time. First we shortly summarize the modelling of reactive transport of a single component (carrier, contaminant, carrier bound contaminant) in a porous medium, then in section 3 we combine the two equations for the contaminant components. The properties of the contaminant’s effective isotherm and its influence on the transport equation are discussed in section